2012
DOI: 10.1155/2012/392457
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Akt Attenuates RPO-Induced Cardioprotection

Abstract: Previous studies have shown that red palm oil (RPO) supplementation protected rat hearts against ischaemia-reperfusion injury. Evidence from these studies suggested that Akt may be partly responsible for the observed protection. The aim of the current study was therefore to prove or refute the involvement of Akt in the RPO-induced cardioprotection by administration of a specific Akt inhibitor (A6730). Male Wistar rats were randomly divided into 2 groups: a control group receiving standard rat chow and an exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Prior to the evaluation of AKT role in eLTP, we assessed the impact of AKT inhibition on basal synaptic activity in acute hippocampal slices using A6730, a potent AKT inhibitor (Hu et al, ; Katengua‐Thamahane et al, ; Nikhil et al, ; Tomas et al, ; You et al, ). A6730 is highly specific to AKT1 and AKT2 isoforms, while having a minimal impact on AKT3 activity (Lindsley et al, ) and a negligible influence on the activity of other enzymes, in contrast to known pan‐AKT inhibitors (Barnett et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Prior to the evaluation of AKT role in eLTP, we assessed the impact of AKT inhibition on basal synaptic activity in acute hippocampal slices using A6730, a potent AKT inhibitor (Hu et al, ; Katengua‐Thamahane et al, ; Nikhil et al, ; Tomas et al, ; You et al, ). A6730 is highly specific to AKT1 and AKT2 isoforms, while having a minimal impact on AKT3 activity (Lindsley et al, ) and a negligible influence on the activity of other enzymes, in contrast to known pan‐AKT inhibitors (Barnett et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…They showed that prolonged dietary feeding with RPO-supplemented diet (~7 g RPO/kg diet) protected the heart against ischemia/reperfusion injury in rats. They used isolated heart models, perfused both in Langendorff technique [ 215 218 ] and working mode [ 212 , 219 ], showing the vascular-independent direct cardioprotective effects of RPO. RPO administration improved cardiac function during reperfusion [ 212 ] and decreased infarct size [ 215 , 216 ].…”
Section: Modulation Of Hypercholesterolemia-induced Oxidative/nitrmentioning
confidence: 99%
“…It is of interest to researchers that new approaches include those that target mitochondrial function and energetic as well as prevention of no-reflow phenomenon [ 43 ]. Besides prevention of excessive ROS, one of the possible mechanisms by which RPO might confer cardiovascular protection during ischemia/reperfusion is via increased phosphorylation of Akt kinase [ 19 , 21 ]. This activation might be especially important in the heart of SHR where the basal NOS activity was significantly elevated [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies were purchased from Cell Signalling (Danvers, MA, USA) and Abcam (Cambridge, UK). Other chemicals were obtained from Bio-RAD and Sigma (St. Louis, MO, USA) [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation